Pemanfaatan Aplikasi Software Sekolah Dalam Mendukung Sistem Informasi Manajemen Berbasis AI di SMK Ma'arif 1 Piyungan (JURNAL ILMIAH TUT WURI HANDAYANI, 2025)
This study aims to determine the utilization of school software applications used to support AI-based management information systems at SMK Ma'arif 1 Piyungan. This research uses a qualitative approach. This research was carried out at SMK Ma'arif 1 Piyungan in 2024. The source of data for this research is informants consisting of public relations officials and school operators as well as documents. The data collection technique uses data triangulation, namely observation, interviews, and document studies. Data analysis was carried out in a qualitative descriptive manner. The results of the study show that SMK Ma'arif 1 Piyungan is in the process of improving the school administration system, especially the school management information system in a better direction, namely by using school software applications. With the existence of school software applications that are specifically designed for school needs, especially in management information systems, the administrative process can be optimized and provide more time for teachers to focus on teaching. School software applications are a comprehensive solution to overcome operational problems while improving the quality of school management information systems. Keywords: Artificial intelligence, School software applications, school management information systems